2002
DOI: 10.1002/jclp.10022
|View full text |Cite
|
Sign up to set email alerts
|

Protective factors related to antisocial behavior trajectories

Abstract: A group of 115 fifth- and sixth-grade Latino students were surveyed at the beginning and the end of the school year before their transition to middle or junior-high school about their engagement in antisocial behaviors and about individual, social, and behavioral protective factors. The best predictors of decreases in antisocial behavior for these students, above and beyond variance for initial ratings and gender, were student perceptions of social support, parent supervision, and classroom participation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 39 publications
(45 reference statements)
5
48
1
3
Order By: Relevance
“…In contrast, disengaged students have lower levels of school satisfaction (Elmore and Huebner 2010). Furthermore, Morrison et al (2002) found that the best predictor of decreases in antisocial behavior for middle school students were student perceptions of social support, parent supervision, and classroom engagement. Additionally, research suggests student engagement might help buffer against poor social-emotional and behavioral outcomes such as school failure and dropout, juvenile delinquency, and substance abuse (Alexander et al 2001;Finn 1989;Manlove 1998).…”
Section: Student Engagementmentioning
confidence: 41%
“…In contrast, disengaged students have lower levels of school satisfaction (Elmore and Huebner 2010). Furthermore, Morrison et al (2002) found that the best predictor of decreases in antisocial behavior for middle school students were student perceptions of social support, parent supervision, and classroom engagement. Additionally, research suggests student engagement might help buffer against poor social-emotional and behavioral outcomes such as school failure and dropout, juvenile delinquency, and substance abuse (Alexander et al 2001;Finn 1989;Manlove 1998).…”
Section: Student Engagementmentioning
confidence: 41%
“…All student and teacher antecedents discussed above are involvedautonomy and autonomy support, competence and structure, and relatedness and involvement (e.g., Salmela-Aro, . When any of these factors are bolstered, rates of delinquency, drop-out, anti-social behaviors, and other undesirable school related outcomes (e.g., teen pregnancy) decrease (Morrison, Robertson, Laurie, & Kelly, 2002;Schwartz, Gorman, Nakmoto, & McKay, 2006). In some studies, a greater effect on student success is shown for students in demographically at-risk populations (e.g., Coll, et al, 1996;Fall & Roberts, 2012).…”
Section: Engagement In Elementary and Secondary Educationmentioning
confidence: 40%
“…An increasing body of research supports the value of protective factors (e.g., connected with teachers and school, empathy, engagement, pro-social peer groups) as a means of addressing students' needs proactively through a competency-based lens [26][27][28][29][30][31]. By identifying students who lack core protective factors relative to others in their school setting, behavioral supports and interventions can be designed and implemented proactively to mitigate risk before externalizing and/ or internalizing behaviors emerge.…”
Section: Building Local Norms Using Protective Factorsmentioning
confidence: 42%